Evaluation principle and method of horizontal grounding electrode based on time‐varying impedance. Issue 2 (3rd January 2021) - Cao, Xiaobin; Wei, Ming; Wang, Manxiang; Liu, Jiacai; Li, Ruifang; Yang, Lin
Abstract: The length of the horizontal grounding electrode is usually extended to decrease the impulse grounding resistance. In this paper, the mechanism for influencing the effective length is revealed by studying the dispersal process of a horizontal electrode and a method for determining the length is proposed. Firstly, the impulse current and the response voltage are measured at different positions. The results are used to analyse the time‐varying characteristics of the impedance in the dispersal process, the mechanism and the factors influencing the effective length. Furthermore, the current propagation process is divided into a wave head process and a wave tail process. The variation rule and influencing factors of the transient impedance are determined. The wave head impedance acts as a dynamic process from the injection impedance to the wave tail impedance, and the injection impedance is not affected by the length of the grounding electrode. The wave tail impedance is constant and is equal to the DC steady‐state impedance. It is proposed that the effective length is caused by two different dispersal processes and it is obtained when the tail impedance is equal to the impulse grounding resistance. These results are highly significant for optimizing the grounding device.